Emerging investigators. Issue 31 (21st August 2015) - Haddleton, David
<x xml:space="preserve">Abstract</x> This themed issue of Polymer Chemistry highlights the work of emerging investigators in the polymer chemistry field. Editor in Chief David Haddleton introduces the issue.